Effect of biochar in enhancing hydrogen production by mesophilic anaerobic digestion of food wastes: The role of minerals. (19th January 2021) - Sugiarto, Yusron; Sunyoto, Nimas M.S.; Zhu, Mingming; Jones, Isabelle; Zhang, Dongke
Abstract: The role of minerals in biochar in promoting hydrogen (H2 ) production by anaerobic digestion of food waste was investigated. The cultures with the addition of biochar, leached biochar, metal sulphate solution and leached biochar combined with metal sulphate solution, respectively, were placed in bench-scale reactors and incubated at incubator at 32 °C. Daily H2 production and volatile fatty acids (VFAs) were measured and the cumulative H2 yield (YH ) and maximum H2 production rate (RH ) were calculated. The microbial analysis was performed using Illumina MiSeq sequencing. Biochar addition significantly increased the maximum YH by 107% and RH by 54%. However, the addition of leached biochar only increased the maximum YH by 39% and RH by 45% than control. The primary elements in biochars that contribute to H2 production (Fe, K and Ca) were shown to increase the acetic acid, butyric acid and prevalence of the H2 producing bacteria Clostridium butyricum . Highlights: Biochar addition increased YH by 107% and RH by 54%. Leached biochar was less effective in promoting H2 production. Minerals in biochar increased VFAs and Clostridium butyricum proportion. Iron species in biochar play a key role in promoting hydrogen production.